Effect of Palm Oil Clinker Powder-Based Geopolymer on Bitumen and Asphalt Mixture Properties - Yaro, N.S.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Emphasis is being devoted to using a modifier in asphalt mixtures production because convention materials cannot withstand current traffic loading and environmental conditions. The asphalt pavement industry is increasingly focusing on sustainability by turning waste materials into alternative raw materials. This study aims to determine the influence of palm oil clinker powder-based geopolymer modifier (POCP-GM) on conventional bitumen and Marshall properties of asphalt mixtures. To produce the geopolymer modifier, the POCP was mixed with the alkali activators, sodium hydroxide (NaOH) pallets, and sodium silicate (Na2SiO2). POCP-GM bitumen (POCP-GMB) was produced using a high-speed mixing technique for 0, 2, 4, 6, and 8 by weight of bitumen. The finding shows that incorporating POCP-GM produced a stiffer blend with decreasing penetration and improved softening point with good storage stability and compatibility in the POCP-GMB. Depending on the Marshall results, it was found that POCP-GMB mixtures possess improved stability relative to the control mixture, and the voids values determined are within the stipulated standard. The mixture's properties improvement can be attributed to geopolymer pozzolanic characteristics, which create strong interactions between the bitumen-geopolymer matrix which gives sufficient coating around the aggregate which improves mixtures properties. The study findings revealed the viability of utilizing geopolymer as a plausible alternative modifier to improve bitumen and asphalt mixtures' performance. From the study findings, 6 POCP-GM can be considered the optimum dosage that improves bitumen and asphalt mixture properties and helps promotes sustainability. Â© 2021 IEEE.